Endocrine Outcomes and Associated Predictive Factors for Somatotrophin Pituitary Adenoma after Endoscopic Endonasal Transsphenoidal Surgery: 10 Years of Experience in a Single Institute - Geng, Yuanming; Dong, Qian; Cong, Zixiang; Zhu, Junhao; Li, Zhenxing; Du, Chaonan; Yuan, Feng; Zeng, Xinrui; Ali, Alleyar; Yang, Jin; Tang, Chao; Ma, Chiyuan (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objective Biochemical remission rates of endoscopic endonasal transsphenoidal surgery (EETS) and its associated predictive factors were evaluated in patients with somatotrophin pituitary adenomas.Methods The patients who underwent EETS in Jinling Hospital were identified between 2011 and 2020. The surgeons' experience, preoperative insulin-like growth factor 1 (IGF-1), basal growth hormone (GH) levels, nadir GH levels, and the tumor characteristics were analyzed for their relationships with endocrine outcomes. Total 98 patients were included for single factor analysis and regression analysis. They were divided into three groups according to the admission chronologic order.Results The overall remission rate of the patients was 57% (56/98) for all the patients over 10 years. In the single factor analysis, we found that the tumor size, cavernous invasion, and sellar invasion were valuable to predict the endocrine outcome after surgery. As for the suprasellar invasion, no significant difference was found between the noninvasive group and the invasive group. The preoperative IGF-1 level (p = 0.166), basal GH level (p = 0.001), and nadir GH level (p = 0.004) were also different between the remission group and the nonremission group in the single factor analysis. The logistic regression analysis indicated that the preoperative nadir GH (odds ratio = 0.930, 95% confidence interval = 0.891–0.972, p = 0.001) was a significant predictor for the endocrine outcomes after surgery.Conclusion The surgeons' experience is an important factor that can affect the patients' endocrine outcomes after surgery. The macroadenomas with lateral invasion are more difficult to cure. Patients with higher preoperative nadir GH levels are less likely to achieve remission.
Keywords: pituitary adenoma; acromegaly; growth hormone; cavernous sinus; invasion; Knosp; endoscopic; transsphenoidal surgery